Biochemical characterization of the venom of Central American scorpion Didymocentrus krausi Francke, 1978 (Diplocentridae) and its toxic effects in vivo and in vitro - Rojas Azofeifa, Daniela (2019)
non-buthid venoms, for which knowledge is scarce. In this work, we characterized the venom of a Diplocentridae species, Didymocentrus krausi, a small fossorial scorpion that inhabits the Tropical Dry Forest of Central America. D. krausi venom soluble fraction contains proteases with enzymatic activity on gelatin and casein. Mass spectrometry and venomic analysis confirmed the presence of elastase-like, cathepsin-O-like proteases and a neprilysin- like metalloproteinase. We did not detect phospholipase A2, C or D, nor hyaluronidase activity in the venom. By homology-based venom gland transcriptomic analysis, NDBPs, a β-KTx-like peptide, and other putative toxin transcripts were found, which, together with a p-benzoquinone compound present in the venom, could potentially explain its direct hemolytic and cytotoxic effects in several mammalian cell lines. Cytotoxicity of D. krausi venom was higher than the effect of venoms from two buthid scorpion species distributed in Costa Rica, Centruroides edwardsii and Tityus pachyurus. Even though D. krausi venom was not lethal to mice or crickets, when injected in mouse gastrocnemius muscle at high doses it induced pathological effects at 24 h, which include myonecrosis, weak hemorrhage, and inflammatory infiltration. We observed an apparent thrombotic effect in the skin blood vessels, but no in vitro fibrinogenolytic activity was detected. In crickets, D. krausi venom induced toxicity and paralysis in short periods of time